Pemberdayaan TPQ Melalui Pelatihan Tahsin Metode Tilawati Berbasis Asset-Based Community Development di Desa Sindangkerta - Amaliyah, Dede Siska; Melinda, Hanna Septia; Aziz Ali Fahmi; Neng Mala; Ai Ratika (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
This community service activity aims to improve the quality of students' reading of the Qur'an through the application of the Tilawati method with an Asset-Based Community Development (ABCD) approach at TPQ Roudhatul Jannah, Sindangkerta Village, Pagelaran District, Cianjur Regency. TPQ previously did not have a structured tahsin learning method so that students' abilities developed unevenly. The implementation of the program is carried out through five stages of ABCD: discovery, dream, design, define & deliver, and destiny. Activities start from identifying community assets, compiling common expectations, training planning, implementing classical and individual Tilawati learning, to evaluating the sustainability of the program through munaqosah. The results showed an increase in the ability of students in the aspects of tajweed, makhraj, and fluency in reading. TPQ teachers are also able to master the Tilawati method so that learning can continue independently after the program is completed. In addition, this activity strengthens collaboration between the community, teachers, and volunteers in creating a more effective learning environment. This program proves that the empowerment of community assets and the application of the Tilawati method are able to improve the quality of tahsin of students while strengthening the sustainability of community-based Qur'an learning.